Factors affecting Umbilical Cord Vitamin D Concentration and Its Association with Maternal Vitamin D Level (International Journal of Integrated Health Sciences, 2024)
Objective: To analyze factors affecting maternal and umbilical cord levels of vitamin D and to understand the correlation between maternal and umbilical cord vitamin D levels.Methods: This was a cross-sectional study conducted at the department of pediatrics of Dr. D. Y. Patil Medical College and Research Centre, Pune, India. Maternal and umbilical cord vitamin D levels were examined in 300 pairs of mother and child over a period of two years. Informed consent was obtained from all participants. The vitamin D level was measured using chemiluminescent immunoassay and classified as either deficient, insufficient or adequate depending on specific cut-offs. Correlations between maternal and neonatal vitamin D levels and demographic factors like religion, socioeconomic status, and sun exposure were also exlored. Statistical tests were performed using the SPSS 21.0 software, with p
Keywords: Fetal development; neonate; pregnancy; vitamin D